Epidemiological Characteristics of Tick-Borne Encephalitis in the Sverdlovsk District over a 20-Year Period - N. M. Kolyasnikova; L. G. Chistyakova; A. V. Ponomareva; A. E. Platonov; V. V. Romanenko; А. A. Ishmukhametov; V. G. Akimkin (Эпидемиология и вакцинопрофилактика)
Relevance. Despite the ongoing program of mass vaccination of tick-borne encephalitis (TBE) for more than 20 years in the Sverdlovsk district, the incidence rate of TBE continues to exceed the average in Russia and the Ural Federal region.Aim. To analyze the main indicators of the manifestation of the epidemic process of TBE in the territory of the Sverdlovsk district under the conditions of planned vaccination over a 20-year period (2002–2021).Materials and methods. The article uses data from federal and regional statistical observations, reporting materials of the Department of Rospotrebnadzor in the Sverdlovsk district for 2002-2021, methods of statistical analysis.Results and discussion. During the study period (2002-2021), 3861 cases of TBE were registered in the Sverdlovsk district, while the highest incidence rate was detected in 2005 – 10.1 per 100 thousand population, and the lowest in 2020 – 1.0 per 100 thousand population. The share of the vector-borne mechanism was 78.4%, the unidentified path – 20.1%, alimentary – 1.5%. Analysis of the seasonal distribution of cases of TBE showed that the incidence is recorded from April to November. Cases of TBE were recorded in all age groups, including the child population. Most often, people aged 60 years old and older (24.6%) were ill with TBE. Among the children's population, the largest share fell on children aged 7–14 years (5.4%). Men of working age prevailed among the patients (66.0%). TBE was mainly registered among the unvaccinated population (81.5%) with a predominance of urban (86.1%). Officials predominated among the sick persons – 29.8%, pensioners made up 22.3%, unemployed – 19.8%. Persons whose work is professionally connected with the forest made up only 0.6%. The ongoing program of mass vaccination of TBE has led to a decrease in the proportion of severe and moderate forms of diseases (focal – 9.8% and meningeal – 24.0%) and an increase in the proportion of febrile (33.8%) and atypical forms (32.4%). Deaths during the studied period were recorded mainly among the adult unvaccinated population.Conclusions. The Sverdlovsk district continues to be a tense natural focus of TBE with a constantly recorded incidence among contingents of different age and social groups. In the absence of highly effective etiotropic drugs for the treatment of TBE, the only strategy for reducing the incidence of TBE, the development of severe forms and deaths in the territory of the Sverdlovsk district is mass vaccination of the population.